PENGEMBANGAN BAHAN AJAR BERBASIS PROJECT BASED LEARNING BERBANTUAN SOFTWARE GEOGEBRA - Dhia Octariani; Isnaini Halimah Rambe (Universitas Islam Sumatera Utara, 2018)
Abstract. This research is a learning device development research that will be used in learning with the Project based Learning (PjBL) model with the help of technology, in this case using Geogebra software. Geogebra Software is a dynamic mathematical software that combines geometry, algebra and calculus can be used as a tool in mathematical learning. Geogebra is a special mathematical program that can be used as a medium for learning mathematics. This research was conducted in one of the high schools in Deli Serdang Regency. Development of learning is done gradually in accordance with step 4D, then the researchers simplify the changing of the four stages (4D) into three stages (3D) is defining, designing, and development.Keywords: Teaching Materials, Project Based Learning (PjBL), Geogebra Software